Empowered psychotherapy : teaching sef-processing : a new approach to the human psyche and its reintegration - Langs, Robert, 1928-2014 (Karnac Books, 1993)
'Self-Processing' is Langs' development of self-analysis. He lays down a detailed technique and ground-rules for using this technique in everyday practice, in order to utilise the encoded impulses and adaptive processes of the client.